The electrocrystallization mechanisms and kinetics of copper onto glassy carbon - Tadesse, Bogale; Addai-Mensah, J.; Fornasiero, D.; Follink, B.; Horne, M.; Ralston, J. (2012)
The nucleation and growth process of crystalline phases by electrocrystallization is of significant interests due to its application in producing thin films of metals and oxides for the fabrication of alloys, integrated circuits and magnetic recording devices with high degree of selectivity and precision. The attractiveness of electrocrystallization emerges from the fact that uniform, thin or multilayer films of various physicochemical properties may be achieved by tuning primary variables such as current density (applied potential), bath composition and temperature. To date, there is a dearth of understanding of the fundamental electrocrystallization mechanisms and kinetics and their links with the structure and properties of thin films (e.g., grain size, morphology, resistivity, hardness and corrosion). The main objective of the present work is to investigate the effect of electrolyte concentration on the mechanisms and kinetics of electrocrystallization and morphology of copper onto glassy carbon electrode. Cyclic voltametric and chronoamperometric results indicated that at lower electrolyte concentrations (5 10-4 - 10-3 M), a 2D, lattice incorporation-limited growth mechanism prevails, resulting in monolayer coverage deposition. At higher electrolyte concentrations (10-2 -10-1 M), a 3D growth mechanism under both charge transfer and volume diffusion limitations was observed. An Atomic Force Microscopy study of the deposit revealed a laterally spread small nuclei at lower concentrations and an island growth at higher concentrations, in agreement with the electrochemical findings.